Sediment transportation in sewerage under control - Dąbrowski , Wojciech; Dąbrowska, Barbara (Instal, 2019)
A literature review of different types of sewerage sediment classification has been presented. Parameters characterizing pollution in sewerage sediments have been compared with values of the same parameters for municipal and combined sewerage wastewaters in dry and wet weather periods. Some attempts of predicting pollution transportation in terms of COD, BOD and ammonia nitrogen values in movable sediments have been described. Two different kinds of sediment traps have been compared.
Keywords: sewerage sediment properties; pollution load; sewerage; sediment traps